THE GOBUSTAN NEOLITHIC CULTURE - Amirhanov, Hizri Amirhanovic (History, Archeology and Ethnography of the Caucasus, 2023)
Based on the study of concrete material, the paper proposes to introduce a new Neolithic archaeological culture in the Caucasus – the Gobustan culture. As the basis for a detailed typological analysis, the author examined numerous collections of stone tools, uncovered from the cultural layers of the Anazaga site. Although known since 1965, these materials have not been the subject of any monographic publication until now. The proposed study considers these collections in the context of synchronous sites of the region and in more broad terms – in the cultural area, which includes Neolithic industries of the studied type. The main typological basis for the identification of the Gobustan Neolithic culture is the type of tools, which is defined by the author as the Uytash point. In functional terms, this item is a peculiar flint arrowhead. The geography of this cultural-defining type includes the area of the Caspian Sea coasts, at least from Gobustan to the place of narrowing of the Caspian lowland on the Dagestan coast in the vicinity of modern Makhachkala. In view of the ambiguity and incompleteness of publications of data on radiocarbon analysis, the chronological framework of the Gobustan culture at the moment has to be discussed using only the concepts of relative age. Based on the possibilities of comparative-typological dating, we suggest to consider the time of its functioning in the period of the 6th and probably the beginning of the 5th millennia BC, approximately synchronously with two other Neolithic cultures of the Eastern Caucasus – Shomutepe and Chokh. At the same time, the Gobustan culture radically differes from the last two not only in terms of material culture, but also in the life-support strategy, characteristic to its bearers.
Keywords: Azerbaijan Republic; Gobustan; Neolithic; archaeological culture; lithic industry; culture-defining type; Uytash point